The short‐term economywide impacts of COVID‐19 in Africa: Insights from Ethiopia - Aragie, Emerta A.; Taffesse, Alemayehu Seyoum; Thurlow, James (African Development Bank, 2021)
The COVID‐19 impact on the global economy combined with partial lockdown measures in Ethiopia represents a large, unprecedented shock to the country's economy. The social accounting matrix (SAM) multiplier model, built on the most up‐to‐date SAM (2017) for Ethiopia, shows that the country suffered a 14.3% loss in GDP (Birr 43.5 billion or US$1.9 billion) during the lockdown period compared to the no‐COVID case during the same period. Nearly two‐thirds of the losses come from the services sector. Although no direct restrictions were imposed on the agriculture sector, which is the primary means of livelihood for most, the sector faces a 4.7% loss in output due to its linkages with the rest of the economy. We find dissimilar income and poverty effects across households by income quintile and level of urbanization. The study also considers two recovery scenarios and generates relevant insights on the potential impacts of COVID‐19 by the end of 2020. The earmarked relief and recovery plan resources can only help the economy to recover if targeted in an efficient way towards sectors most affected by COVID‐19, and further resources are mobilized to support strategic sectors—those with the highest economywide multiplier effects—and vulnerable communities.